Potential of a bivalent vaccine for broad protection against enterovirus 71 and coxsackie virus 16 infections causing hand, foot, and mouth disease - Yi, Eun Je; Kim, Young In; Song, Jae Hyoung; Ko, Hyun Jeong; Ahn, Sung Hyun; Lee, Hyoung Jin; Suh, Bohyun; Yu, Jaelim; Park, Jeehye; Lee, Yoon Jung; Jung, Eun Ju; Chang, Sun Young (Vaccine, 2023)
Hand, foot, and mouth disease (HFMD) is a highly contagious viral infection that is mainly caused by enterovirus 71 (EV71) and coxsackievirus 16 (CVA16). As there are no specific therapeutics for HFMD, the development of a bivalent vaccine is required to cover a broad range of infections. In this study, the effectiveness of novel monovalent and bivalent vaccines targeting EV71 C4a and CVA16 was investigated for their ability to prevent viral infections in neonatal human scavenger receptor class B member 2 (hSCARB2) transgenic mice. As hSCARB2 serves as a key viral receptor for EV71, these transgenic mice are susceptible to EV71 strains and facilitate viral binding, internalization, and uncoating processes. Antisera prepared by vaccine immunization were transferred to 2-day-old hSCARB2 transgenic mice, which were then infected with EV71 C4a or CVA16 virus. The antisera generated by each monovalent or bivalent vaccine effectively protected against EV71 C4a and CVA16 infections. The examination of tissue damage and viral contents in various organs indicated that both monovalent and bivalent antisera reduced EV71 C4a viral load in the brainstem, and no significant tissue damage was observed. During CVA16 infection, the monovalent and bivalent antisera significantly reduced viral contents in both the brainstem and muscles. These results suggest that passive immunity by monovalent and bivalent antisera can effectively protect against EV71 C4a and CVA16 infections. Thus, the development of a bivalent vaccine that can provide broad protection against both CV and EV infections may be a promising strategy in preventing HFMD.
Keywords: Animals; Enterovirus A, Human; Hand, Foot and Mouth Disease; Humans; Immune Sera; Mice; Mice, Transgenic; Vaccines, Combined; Bivalent vaccine; Coxsackievirus A16; Enterovirus71 C4a; Hand, foot, and mouth disease; hSCARB2